PAK5 Induces EMT and Promotes Cell Migration and Invasion by Activating the PI3K/AKT Pathway in Ovarian Cancer - Diyou Li; Yinglin Pan; Yating Huang; Ping Zhang; Xuhong Fang (Analytical Cellular Pathology)
Ovarian cancer is the most lethal gynecologic cancer and currently ranks fifth in causing cancer-related deaths among women. P21cdc42/rac1-activated kinase 5 (PAK5) is a newly identified protein that has been indicated to have oncogenic potential. The present study investigated the expression level of PAK5 in clinical ovarian cancer and the functional roles of PAK5 in ovarian cancer progression. It was initially found that PAK5 was highly expressed in ovarian cancer tissues, particularly in patients with distant metastasis. Higher expression of PAK5 predicted poor survival fates in patients with ovarian cancer (p=0.008). Knockdown of PAK5 in SKOV3 cells caused epithelial cell phenotypes, whereas overexpression of PAK5 led to remarkable mesenchymal cell phenotypes in A2780 cells. When PAK5 was depleted from SKOV3 cells, cells exhibited impaired wound recovery abilities. Cell migration and invasion abilities were also significantly inhibited. On the contrary, when PAK5 was overexpressed in A2780 cells, the wound recovery ability was enhanced by 68%. Cell migration and invasion abilities were consistently increased to approximately 2-fold. After knockdown of PAK5, the phosphorylation levels of PI3K p85 at Tyr458 and its downstream AKT at Ser473 were both decreased. The total protein of PI3K and AKT as well as the phosphorylation level of AKT at Thr308 remained unaffected. These data suggested that PI3K induced epithelial-to-mesenchymal transition and promoted cell migration and invasion by activating the PI3K/AKT pathway in ovarian cancer. The oncogenic potential of PAK5 in ovarian cancer might suggest that any therapeutic strategies targeting PAK5 had the promising value for ovarian cancer treatment.